(3GdJShjb GdeYGUQ (B:s (3GdeaGgje h GdSjGSGJ (B/s - (3GdOOG, Ydj ehSis ((3YeGf(B: s (3GdHOGjI ddfTQ hGdJhRjY(B, s, 2010)
(3eaghe GdJShjb h JWhQg , GdHjFI GdJShjbjI h JbSje GdShb h GdeYGjjQ h GdeJWdHGJ GdNGUI HhVY JLRFI aGYdjI GdShb , Sdhc GdeSJgdc , SjGSGJ h bQGQGJ GdSdY h JWhjQ GdSdY GdLOjOI , OQGSI GdJSYjQ h GdJQhjL , GdJShjb GdGdcJQhfjs
(3agQS GdLOGhd h GdCTcGd U(B. 265 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdESJQGJjLjI GdJfGaSjIs; (3GdJShjbs; (3GdJShjb GdEdcJQhfjs